Associativismo negro em laguna e a construção identitária: irmandade, sociedades musicais e clubes negros (1870 a 1950) - Rosa, Júlio César (Universidade do Vale do Rio dos Sinos, 2021)
This study has the objective of analyzing the foundation of the, Cruz e Sousa Recreative Society and Uniao Operaria, built by the afro-descendants diaspora in Laguna, Santa Catarina, in the post-abolition period between 1870 and 1950. Such study has the intention to learn about the tensions between the people selfproclamed Mulattos and Blacks, understanding their identities from the social place occupied by each member of the two Associations. We aim to understand what meant to be a "mulatto" or a "black" for those men and women in that context, and what made them want to silence and/or to hide their racial-ethnicity. Understanding the confrontation and memory-related problems, we believe that, when summoned by the interviewer, it can put in evidence experiences of an era that brings up the history of common people which have been ostracized and/or ignored by traditional history in the course of historic processings. In this way, we intend to perceive the construction of these identities, and understand how this memory was generated and reinforced in such social spaces. We intend to evidenciate the organization of the recreational clubs in an attempt to comprehend its dinamics, strategical places of associativism, the possible relationship networks with other clubs, their individual and collective projects, their aspirations and expectations toward social ascension (climbing), visibility and respectability in the battle for citizenship in Laguna during the first half of the XX century.
Keywords: Associativismo negro; Pós-abolição; Sociedade Recreativa União Operária; Clube Literário Cruz e Sousa; Laguna; Black associativism; Post-abolition; ACCNPQ::Ciências Humanas::História